If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(x + -1) = 11.2 Reorder the terms: 7(-1 + x) = 11.2 (-1 * 7 + x * 7) = 11.2 (-7 + 7x) = 11.2 Solving -7 + 7x = 11.2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + 7x = 11.2 + 7 Combine like terms: -7 + 7 = 0 0 + 7x = 11.2 + 7 7x = 11.2 + 7 Combine like terms: 11.2 + 7 = 18.2 7x = 18.2 Divide each side by '7'. x = 2.6 Simplifying x = 2.6
| =5x-3[(11x-5)-(x-2)] | | 3-2(a-1)=4a-13 | | 5.2=2c-9 | | z^2+2iz-3i=0 | | 4(x-2)+12=2(5-2x) | | 20+X=51 | | 6e-8=16 | | -y+7(6+2y)= | | 2x+12=68+6x | | 5x+2y^2=3 | | (h-78)/9(1)+(-13)+50-(78*.25)=-20 | | 4(2x-1)=-28 | | 4(x-8)=0 | | 22=t | | 8+1.25=16.75 | | 3x+38=16+x | | 184+2h=986 | | x+3x-1+x+15= | | 3x^2-6x+11000=0 | | 4x(x)=49 | | 2x^6*x-95=0 | | 0.2p-10= | | 6-4x=x+7(x+8) | | 144=16t | | 28(p+30)=3,108 | | 8.32+7.76-10.09= | | 3,108=28(p+30) | | x+(3x+4)=112 | | 6(2x-3)=24 | | X+(x-21)=157 | | 2x+12+7x-1=x | | 2(3x+3)=11x+3-5x+3 |